13y-4=19y+2

Simple and best practice solution for 13y-4=19y+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13y-4=19y+2 equation:


Simplifying
13y + -4 = 19y + 2

Reorder the terms:
-4 + 13y = 19y + 2

Reorder the terms:
-4 + 13y = 2 + 19y

Solving
-4 + 13y = 2 + 19y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-19y' to each side of the equation.
-4 + 13y + -19y = 2 + 19y + -19y

Combine like terms: 13y + -19y = -6y
-4 + -6y = 2 + 19y + -19y

Combine like terms: 19y + -19y = 0
-4 + -6y = 2 + 0
-4 + -6y = 2

Add '4' to each side of the equation.
-4 + 4 + -6y = 2 + 4

Combine like terms: -4 + 4 = 0
0 + -6y = 2 + 4
-6y = 2 + 4

Combine like terms: 2 + 4 = 6
-6y = 6

Divide each side by '-6'.
y = -1

Simplifying
y = -1

See similar equations:

| 9x-3=1+8x | | 24-4x=-32 | | 6x=5x | | 1+4x=34+x | | 24-4x=32 | | 5(2y-3)=9(y+4) | | (5X-7)+(4X+11)=14-X | | 5x=4x-1 | | x^2-7x=20 | | x^2-7x-20=-200 | | x^2-7x-20=0 | | 81-6x=10x-5x | | 5x^2+8x+42=0 | | 6x+33=16x-67 | | 12+1.5a=2a | | 5(x-6)-6(x-5)=x+2-(x-3) | | 12n-24=14n+28 | | x^3+x^2=25 | | 7(1-s)=-2(5s+4)+6s | | 3n+11=-16 | | 4y-9=18y+5 | | 2f-6=75+24 | | 10x+10=8x+2 | | 4(2-x)-3(7x+5)+6(3x-1)=2(8-x) | | 8x+9=5x+30 | | 3(x-2)-4(2x-3)=2(3x-1)-3(3x+1)+3 | | 3(2-3x)-2(5x-1)-3-2x=0 | | x-2(x-3)=5x+3(2x+2) | | 9x+24=5x+120 | | 5(3-x)-3(5-x)=0 | | -11=11(c-3) | | 99-5x=31x+15 |

Equations solver categories